Influence of electric traction system on power grid harmonics. (May 2019) - Tan, Meng; He, Dongshan; Wen, Jun; Geng, Xiaohong; Wang, Sichao
Abstract: This paper analyzes the traction power supply system and traction substation of electrified railway. Due to the use of a large number of power electronic devices, the electric locomotive has strong nonlinear characteristics. Focusing on harmonics, this paper studies the harmonics generated by AC-DC and AC-DC-AC electric locomotives respectively. Based on this, The mathematical model of the power supply system of electrified traction locomotive is established, and the harmonic model is established. The simulation results are in good agreement with the actual conditions.